Shiny things : reflective surfaces and their mixed meanings - Diepeveen, Leonard, 1959-; Van Laar, Timothy (Intellect, 2021)
Discusses meanings of shininess in art and in culture generally. Shininess is physically and metaphorically present in the construction of concepts such as utopia, the sublime, and camp; and the way its affects, rooted in excess produce irony, anxiety, pleasure and kitsch. A compelling subject that instantly attracts and fascinates. 54 b/w illus.